Association between time-varying weighted hemoglobin and all-cause mortality in patients with acute myocardial infarction-related cardiogenic shock - Xia Liu; Tianbo Gong; Yongpeng Zhang (Frontiers in Cardiovascular Medicine)
Background and aimsAnemia has been implicated in prognosis across ischemic heart diseases. This study aimed to investigate the association between time-weighted average hemoglobin (TWA-Hb) and all-cause mortality in patients with acute myocardial infarction-related cardiogenic shock (AMI-CS).Methods and resultsWe conducted a retrospective analysis of 765 patients diagnosed with AMI-CS using data from the MIMIC-IV database (2008–2019). Kaplan–Meier survival analysis demonstrated that lower TWA-Hb levels were associated with higher cumulative mortality rates at 28 days, 90 days, 6 months, and 1 year (log-rank P = 0.002, 0.006, 0.048, and 0.005, respectively). Landmark analyses further revealed a sustained increase in mortality risk associated with lower TWA-Hb during the 28-day to 1-year follow-up period. Multivariable Cox regression analysis identified low TWA-Hb as an independent predictor of mortality risk at 90 days (P = 0.026), 6 months (P = 0.023), and 1 year (P = 0.021). Each one-unit increase in TWA-Hb was associated with a 0.93-, 0.76- and 0.71-fold decrease in the risk of 90-day, 6-month, and 1-year mortality, correspondingly. Subgroup analyses stratified by age, BMI, and comorbidities consistently supported these findings (all P < 0.05).ConclusionLow TWA-Hb is associated with long-term mortality in patients with AMI-CS. These findings imply that the application of this indicator in clinical practice could improve long-term risk stratification.